TEMA, KARAKTER, LATAR BUDAYA, DAN RESISTENSINYA DALAM DONGENG TIMUN EMAS DAN KOMIK SHINGEKI NO KYOUJIN KARYA HAJIME ISHIYAMA - Sri Wahyuningtyas (CARAKA, 2015)
Timun Emas tales story and SNK comic are constructed by the same theme and character but in different culture between Java (Indonesia) and Japan. That situation also represented a different way of life which is relevant to their problem and what could they do to solve the problem. Javanese people inclined to do prihatin ways. Indonesian people preferred to solve the problem with negotiation and God should be the final of problem-solving. In different ways, people of Japan inclined to do competition and discipline. They really admire the time and nothing for negotiation which is waste the time. The other principle of Japanese society is strong determination.